Serum from young, sedentary adults who underwent passive heat therapy improves endothelial cell angiogenesis via improved nitric oxide bioavailability. Issue 2 (3rd April 2019) - Brunt, Vienna E.; Weidenfeld-Needham, Karen M.; Comrada, Lindan N.; Francisco, Michael A.; Eymann, Taylor M.; Minson, Christopher T.
ABSTRACT: Rationale : Passive heat therapy improves vascular endothelial function, likely via enhanced nitric oxide (NO) bioavailability, although the mechanistic stimuli driving these changes are unknown.Objective : To determine the isolated effects of circulating (serum) factors on endothelial cell function, particularly angiogenesis, and NO bioavailability.Methods and Results : Cultured human umbilical vein endothelial cells (HUVECs) were exposed to serum collected from 20 healthy young (22 ± 1 years) adults before (0 wk), after one session of water immersion (Acute HT), and after 8 wk of either heat therapy (N = 10; 36 sessions of hot water immersion; session 1 peak rectal temperature: 39.0 ± 0.03°C) or sham (N = 10; 36 sessions of thermoneutral water immersion). Serum collected following acute heat exposure and heat therapy improved endothelial cell angiogenesis (Matrigel bioassay total tubule length per frame, 0 wk: 69.3 ± 1.9 mm vs. Acute HT: 72.8 ± 1.4 mm, p = 0.04; vs. 8 wk: 73.0 ± 1.4 mm, p = 0.03), with no effects of sham serum. Enhanced angiogenesis was NO-mediated, as addition of the NO synthase (NOS) inhibitor L-NNA to the culture media abolished differences in tubule formation across conditions (0 wk: 71.3 ± 1.8 mm, Acute HT: 71.6 ± 1.9 mm, 8 wk: 70.5 ± 1.6 mm, p = 0.69). In separate experiments, we found that abundance of endothelial NOS (eNOS) was unaffected by Acute HT serum (p = 0.71), but increased by 8 wk heat therapy serum (1.4 ± 0.1-fold from 0 wk, p < 0.01). Furthermore, increases in eNOS were related to improvements in endothelial tubule formation (r 2 = 0.61, p < 0.01).Conclusions : Passive heat therapy beneficially alters circulating factors that promote NO-mediated angiogenesis in endothelial cells and increase eNOS abundance. These changes may contribute to improvements in vascular function with heat therapy observed in vivo . Abbreviations : Ang-1: angiopoietin-1; ANOVA: analysis of variance; bFGF: basic fibroblast growth factor; CV: cardiovascular; CVD: cardiovascular diseases; eNOS: endothelial nitric oxide synthase; HSPs: heat shock proteins; HT: heat therapy; HUVECs: human umbilical endothelial cells; L-NNA: Nω-nitro-L-arginine; MnSOD: manganese superoxide dismutase; NO: nitric oxide; NOS: nitric oxide synthase; PBMCs: peripheral blood mononuclear cells; RM: repeated measures; sFlt-1: soluble VEGF receptor; SOD: superoxide dismutase; TGF-β: transforming growth factor- β; VEGF: vascular endothelial growth factor